Self-consciousness concept and assessment in self-report measures - DaSilveira, Amanda; DeSouza, Mariane L.; Gomes, William B. (Frontiers in Psychology, 2015)
This study examines how self-consciousness is defined and assessed using self-report questionnaires (Self-Consciousness Scale, Self-Reflection and Insight Scale, Self-Absorption Scale, Rumination-Reflection Questionnaire, and Philadelphia Mindfulness Scale). Authors of self-report measures suggest that self-consciousness can be distinguished by its private/public aspects, its adaptive/maladaptive applied characteristics, and present/past experiences. We examined these claims in a study using 602 young adults to whom the aforementioned scales were administered. Data were analysed as follows: (1) correlation analysis to find simple associations between the measures; (2) factorial analysis using Oblimin rotation of total scores provided from the scales; and (3) factorial analysis considering the 102 items of the scales all together. It aimed to clarify relational patterns found in the correlations between self-consciousness scales, and to identify possible latent constructs behind these scales. Results support the adaptive/maladaptive aspects of self-consciousness, as well as distinguish to some extent public aspects from private ones. However, some scales that claimed to be theoretically derived from the concept of Private Self-Consciousness correlated with some of its public self-aspects. Overall, our findings suggest that while self-reflection measures tend to tap into past experiences and judged concepts that were already processed by the participants' inner speech and thoughts, the Awareness measure derived from Mindfulness Scale seems to be related to a construct associated with present experiences in which one is aware of without any further judgment or logical/rational symbolization. This sub-scale seems to emphasize the role that present experiences have in self-consciousness, and it is argued that such a concept refers to what has been studied by phenomenology and psychology over more than one hundred years: the concept of pre-reflective self-conscious.